Negotiating Moral Values through Interpersonal Communication: Student–Teacher Interaction in an Islamic Boarding School - Efendi, Harun Ar; Sumarlan, Iman (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study aims to analyze the role of students’ interpersonal communication with teachers in fostering moral development (akhlak) at Al-Barohin Islamic Boarding School. Employing a qualitative approach with a case study design, this research examines how interpersonal communication functions as a medium for moral and character education in the daily life of an Islamic boarding school. Data were collected over a four-month period through participant observation, in-depth interviews, and documentation, involving seven informants consisting of teachers, students, and a boarding school caregiver. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that students’ interpersonal communication plays a significant role in moral development when characterized by openness, empathy, supportiveness, positiveness, and equality. Dialogical and participatory communication patterns foster mutual trust, strengthen teacher-student relationships, and support the internalization of Islamic moral values such as discipline, responsibility, and self-awareness. Students are positioned not merely as passive recipients of moral instruction but as active communicative agents who contribute meaningfully to the moral education process through continuous interaction with teachers. This study concludes that effective interpersonal communication between students and teachers forms a fundamental foundation for sustainable moral education in Islamic boarding schools and highlights the importance of student agency in value-based educational communication.